Long Non-coding RNA FENDRR Acts as a miR-423-5p Sponge to Suppress the Treg-Mediated Immune Escape of Hepatocellular Carcinoma Cells - Zhenyu Yu; Hui Zhao; Xiao Feng; Haibo Li; Chunhui Qiu; Xiaomeng Yi; Hui Tang; Jianwen Zhang (Elsevier, 2019)
Long non-coding RNAs (lncRNAs) have been known to partake in the development and the immune escape of hepatocellular carcinoma (HCC). The initial microarray analysis of GSE115018 expression profile revealed differentially expressed lncRNA fetal-lethal non-coding developmental regulatory RNA (FENDRR) in HCC. Therefore, this study's main purpose was to explore the mechanism of tumor suppressor lncRNA FENDRR in regulating the immune escape of HCC cells. Notably, it was further validated through this study that lncRNA FENDRR competitively bound to microRNA-423-5p (miR-423-5p), and miR-423-5p specifically targeted growth arrest and DNA-damage-inducible beta protein (GADD45B). The effects that lncRNA FENDRR and miR-423-5p have on the cell proliferation and apoptosis, the immune capacity of regulatory T cells (Tregs), and the tumorigenicity of HCC cells were examined through overexpressing or the knocking down of lncRNA FENDRR and miR-423-5p both in vitro and in vivo. Subsequently, lncRNA FENDRR and GADD45B were revealed to have poor expressions in HCC. Meanwhile, miR-423-5p was highly expressed in HCC. Importantly, overexpressed lncRNA FENDRR and downregulated miR-423-5p diminished cell proliferation and tumorigenicity, and promoted apoptosis in HCC cells, thus regulating the immune escape of HCC mediated by Tregs. Taken conjointly, lncRNA FENDRR inhibited the Treg-mediated immune escape of HCC cells by upregulating GADD45B by sponging miR-423-5p. Keywords: long non-coding FENDRR, microRNA-423-5p, GADD45B, hepatocellular carcinoma, immune escape